Membangunkan Keselamatan Kediaman Menggunakan IC DTMF - Chai, Yu Leong (Universiti Sains Malaysia, 2006)
Nowadays, the electronic security systems are widely used in automobiles, offices, shops or home. Unfortunately, most of the electronic security systems are give out sound or light signals, but not give kind of report to the user or police. To overcome this weakness of the typical electronic security systems, another home security system that can automatically report the home situation to the users and/or police by using telephone we developed. This system acts as an interface between the telephone line and a sensor such as a temperature sensor or motion detector. It will automatically inform the user or police through the home telephone line when a break in or a fire occurs. Besides reporting the situation at home, the security system should be able to remotely control using a telephone call. Although the home owner is not at home, he/she still can switch on or switch off the light and home electrical appliance. Therefore, the possibility of house break in will be reduced. Since the system is connected to the telephone line, a telephone was incorporated into the system. LCD display is included to show the menu and memory to store the phone number. The system uses MC34010 integrated DTMF transceiver IC to make a call and MT8870D integrated DTMF receiver IC to manage the remote control function. A microcontroller AT89S52 is used to control the 3 main functions of the system. The concept of the DTMF and telephone line will be discussed in this report. The hardware design and firmware design are also included in this report. Finally, the hardware is soldered on a PCB and the firmware is loaded into a microcontroller to run the system.